Front Cover: Nucleolipids of the Nucleoside Antibiotics Formycins A and B: Synthesis and Biomedical Characterization Particularly Using Glioblastoma Cells (C&B 4/2019). Issue 4 (21st March 2019) - Rosemeyer, Helmut; Knies, Christine; Hammerbacher, Katharina; Bender, Eugenia; Bonaterra, Gabriel A.; Hannen, Ricarda; Bartsch, Jörg W.; Nimsky, Christopher; Kinscherf, Ralf
Abstract : Front Cover . Nocardia species such as Nocardia interforma as well as Streptomyces species, e.g ., Streptomyces lavendulae, produce the C‐nucleoside antibiotics Formycin A and B. The first was ketalized with ethyl levulinate at its O ‐2', 3'‐erythro‐pentofuranosyl moiety followed by a H(N‐1) alkylation with all‐ trans ‐farnesylbromide. The resulting nucleolipid as well as congeners were tested against a series of human glyoblastoma cell lines. It was demonstrated that particularly the Formycin A nucleolipid shown processes promising anti‐tumor properties with profound cytotoxic effects as reported by Rosemeyer et al . in their full paper at 10.1002/cbdv.201900012 .